Synthesis of Cobalt Oxide on FTO by Hydrothermal Method for Photoelectrochemical Water Splitting Application - Siti Nurul Falaein Moridon; Mohd Nur Ikhmal Salehmin; Khuzaimah Arifin; Lorna Jeffery Minggu; Mohammad B. Kassim (Applied Sciences, 2021)
Cobalt oxide thin films were successfully grown directly on fluorine-doped tin oxide glass substrates through a simple, green, and low-cost hydrothermal method. An investigation into the physicochemical characteristics and photoelectrochemical (PEC) properties of the developed cobalt oxide thin film was comprehensively performed. At various annealing temperatures, different morphologies and crystal phases of cobalt oxide were observed. Microflowers (Co3O4) and microflowers with nanowire petals (Co3O4/CoO) were produced at 450 °C and 550 °C, respectively. Evaluation of the PEC performance of the samples in KOH (pH 13), Na2SO4 (pH 6.7), and H2SO4 (pH 1) revealed that the highest photocurrent −2.3 mA cm−2 generated at −0.5 V vs. reversible hydrogen electrode (RHE) was produced by Co3O4 (450 °C) in H2SO4 (pH 1). This photocurrent corresponded to an 8-fold enhancement compared with that achieved in neutral and basic electrolytes and was higher than the results reported by other studies. This promising photocurrent generation was due to the abundant source of protons, which was favorable for the hydrogen evolution reaction (HER) in H2SO4 (pH 1). The present study showed that Co3O4 is photoactive under acidic conditions, which is encouraging for HER compared with the mixed-phase Co3O4/CoO.